Impact and significance of pretreatment on the fermentable sugar production from low-grade longan fruit wastes for bioethanol production - Tu Vy Thuy Nguyen (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. The feasibility of bioethanol production from low-grade longan fruit waste material was recently studied as a novel substrate for bioethanol production. First, hydrothermal pretreatment followed by enzymatic hydrolysis converted both the cellulosic and hemicellulosic biomass of the low-grade longan fruit wastes into fermentable sugars, which eventually produced ethanol by yeast fermentation. Therefore, an optimal condition of hydrothermal residence time and pretreatment concentration was determined to obtain the high release of sugars. An experimental design was constructed with the Central Composite Design (CCD) response surface method using factors of the hydrothermal residence time and pretreatment concentration in constant temperature and time. The results revealed optimum reducing sugar yield of 240.396 g/L (R2 = 0.9989), sugar productivity of 240.396 g/L.day (R2 = 0.9763), and sugar yield coefficient of 24.04 g/g (R2 = 0.9989). The highest ethanol yield (16.74 g/L) was achieved at 24 h of fermenting time. These results show that low-grade longan fruit wastes are an excellent feedstock for producing ethanol that could be either used as biofuel or as a beverage.